2020
DOI: 10.1017/s0950268820002010
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of clinical features in 134 coronavirus disease 2019 cases

Abstract: We aimed to describe the clinical features in coronavirus disease 2019 (COVID-19) cases. We studied 134 critically ill COVID-19 cases from 30 December 2019 to 20 February 2020 in an intensive care unit (ICU) at Wuhan Jinyintan Hospital. Demographics, underlying diseases, therapy strategies and test results were collected and analysed from patients on admission, admission to the ICU and 48 h before death. The non-survivors were older (65.46 (s.d. 9.74) vs. 46.45 (s.d. 11.09)) and were more likely to have underl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 8 publications
2
38
1
Order By: Relevance
“…( A ) Blood group O odd ratios (ORs) of COVID-19 relative to the other blood groups and blood group O frequencies at various geographical locations. Odd ratios were obtained from the works in [ 1 , 2 , 3 , 6 , 9 , 10 , 11 , 14 , 17 , 18 , 19 , 22 , 24 ], and the frequencies of blood group O were those reported in the groups of controls of the corresponding studies, representing frequencies in the local populations. OR values in populations where frequencies of blood group O are below and above 40% (O < 0.4 and O > 0.4, respectively) were compared by a two-tailed Mann–Whitney test.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…( A ) Blood group O odd ratios (ORs) of COVID-19 relative to the other blood groups and blood group O frequencies at various geographical locations. Odd ratios were obtained from the works in [ 1 , 2 , 3 , 6 , 9 , 10 , 11 , 14 , 17 , 18 , 19 , 22 , 24 ], and the frequencies of blood group O were those reported in the groups of controls of the corresponding studies, representing frequencies in the local populations. OR values in populations where frequencies of blood group O are below and above 40% (O < 0.4 and O > 0.4, respectively) were compared by a two-tailed Mann–Whitney test.…”
Section: Figurementioning
confidence: 99%
“…Thus, soon after the beginning of the pandemic a publication from Wuhan, China, reported a higher risk of infection for people of blood group A, and inversely a lower risk for people of blood group O [ 1 ]. Since then, associations with the ABO blood groups have been described in several additional publications from China as well as many other locations from Asia, the Middle East, Europe, and North America [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Associations between ABO phenotypes were described with either the risk of infection or disease severity, although most studies did not explicitly separate these two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…It is now rather well documented through a large set of studies that blood group A individuals are at a higher risk of COVID-19 than individuals of blood group O, whilst blood group B seldom shows significant odd ratios relative to the other blood groups ( Aktimur et al, 2020 ; Barnkob et al, 2020 ; Chegni et al, 2020 ; Ellinghaus et al, 2020 ; Göker et al, 2020 ; Latz et al, 2020 ; Leaf et al, 2020 ; Li et al, 2020 ; Muniz-Diaz et al, 2020 ; Shelton et al, 2020 ; Sohlpour et al, 2020 ; Valenti et al, 2020 ; Wu et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020 ; Zhao J. et al, 2020 ; Zietz et al, 2020 ). We recently observed that anti-A and anti-B agglutinating natural antibodies were significantly lower in COVID-19 patients compared with controls ( Deleers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, group O individuals possess anti-A and anti-B antibodies that could have protected them from viral particles emitted by either blood group A or B patients. Interestingly, a large number of observations indicate that blood group O individuals have a lower risk of COVID-19, whereas blood group A individuals appear to be at a higher risk ( Cheng et al, 2005 ; Abdollahi et al, 2020 ; Ahmed et al, 2020 ; Aljanobi et al, 2020 ; Barnkob et al, 2020 ; Chegni et al, 2020 ; Delanghe et al, 2020 ; Dzik et al, 2020 ; Ellinghaus et al, 2020 ; Fan et al, 2020 ; Franchini et al, 2020 ; Gallian et al, 2020 ; Göker et al, 2020 ; Hoiland et al, 2020 ; Latz et al, 2020 ; Leaf et al, 2020 ; Li et al, 2020 ; Muniz-Diaz et al, 2020 ; Niles et al, 2020 ; Padhi et al, 2020 ; Ray et al, 2020 ; Roberts et al, 2020 ; Shelton et al, 2020 ; Sohlpour et al, 2020 ; Valenti et al, 2020 ; Wu et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020 ; Zhao J. et al, 2020 ; Zietz et al, 2020 ). Only a few studies failed to find any association between ABO types and COVID-19, likely depending on study design ( Boudin et al, 2020 ; Focosi et al, 2020 ; Pairo-Castineira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of antibiotics consisting of such applied to COVID-19 in China and other countries have been reported to inhibit mitochondrial activity, DNA synthesis, and biogenesis ( Tyszka et al, 2020 ). These antimicrobial agents can affect mitochondrial function and ATP production and also induce cell death pathways ( Surbatovic et al, 2013 ; Singer, 2014 ; Zhang et al, 2020 ). For example, azithromycin that has been administered to treat patients with COVID-19 could cause mitochondrial toxicity, overproduction of reactive oxygen species (ROS), and DNA oxidative damage ( Tyszka et al, 2020 ).…”
Section: Antimicrobial Resistancementioning
confidence: 99%